Scope for improvement of small ruminant production in the Sahel - Williams, Timothy O. (CAB International, 1993)
This chapter investigates the options for improving the performance of small ruminants interms of their contribution to household incomes. The characteristics of the existing production system are first sketched in order to identify the resource requirements and constraints of the system. Based on this imformation, a steady-state flock model is then developed and used to assess the impact of variation in growth, reproduction and mortality rates production. The model treats small ruminants as capital goods and the time-dependent nature of ILCA scientists from long-term studies of agropastoral systems in semiarid areas of central Mali are used to construct the model and to generate baseline solutions with which to compare the impact of proposed improvements. The model provides a device for analysing the performance of the existing system and for assessing the likely magnitude of various interventions. It can thus serve as a tool in the design of livestock research, and can provide guidance as to which of the possible new interventions are worth pursuing and which are not. The theoretical model on which the analysis is based is presented, followed by a description of the data sources. Results are presented and the chapter concludes with a discussion on the scope for sustainable small ruminant production in the Sahel.